A Colon‐Targeted Adsorbent (DAV132) Does Not Affect the Pharmacokinetics of Warfarin or Clonazepam in Healthy Subjects. Issue 8 (12th January 2021) - Pinquier, Jean‐Louis; Varastet, Marina; Meyers, Dismas; Sayah‐Jeanne, Sakina; Féger, Céline; Gaumétou, Olivia; Corbel, Tanguy; de Gunzburg, Jean; Mentré, France; Ducher, Annie
Abstract: DAV132 is a novel colon‐targeted adsorbent that prevents the deleterious impact of antibiotics on gut microbiota without modifying their systemic availability. A randomized, Latin‐square crossover, open‐label trial with 2 substudies in 18 and 24 healthy volunteers evaluated the pharmacokinetic (PK) bioequivalence of warfarin, a drug with a narrow therapeutic index (NTI), and clonazepam, both widely used for the treatment of chronic conditions, with or without coadministration of DAV132 7.5 g. PK parameters observed with single doses of 5 mg warfarin and 1 mg clonazepam when administered alone did not differ with the PK parameters when administered concomitantly with or 1 hour before DAV132. Geometric mean ratios (GMRs) for S‐warfarin, R‐warfarin, and clonazepam Cmax were 102.0, 102.8, and 91.9, respectively, after concomitant administration and 106.5, 107.5, and 95.0, respectively, when administered 1 hour before DAV132. After concomitant administration, GMRs for S‐warfarin, R‐warfarin, and clonazepam AUClast were 100.5, 100.2, and 94.9, respectively, and 101.9, 101.8, and 101.3, respectively, when administered 1 hour before DAV132. All GMR 90% confidence intervals fell within the prespecified 80% to 125% limit for bioequivalence, indicating a lack of drug‐drug interaction. In conclusion, DAV132 did not affect the systemic exposure of 2 NTI drugs absorbed in the proximal intestine.